THE EFFECT OF BUDGET GOAL CLARITY, INTERNAL CONTROL SYSTEMS, AND QUALITY OF HUMAN RESOURCES ON THE VILLAGE CHIEF PERFORMANCE WITH ACCOUNTABILITY AND ORGANIZATIONAL COMMITMENT AS THE MODERATING VARIABLES - YANTI, RIZKE WILI; SARI, RIA NELLY; WATI, VINCE RATNA (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2021)
This study aims to examine and analyze the effect of budget goal clarity, internal control systems, and quality of human resources on the village chief performance with accountability and organizational commitment as the moderating variables. The population of this study is 218 village chief in Kuantan Singingi Regency. This study applied purposive sampling method and 130 chief villages were selected as a sample. The study used primary data and applied Moderrated Regression Analysis (MRA) by using SPSS 23th version to test the hyphoteses. The result of this study shows that budget goal clarity, internal control systems, and quality of human resources affect the village chief performance. Futhermore, the result shows that accountability and organizational commitment strengthen the effect of budget goal clarity, quality of human resources and internal control systems on the village chief performance.